Servant Leadership in Islamic Education: Fostering Teacher Collaboration and Enhancing Student Academic Outcomes - Putri Nur Indah Elviana; Ahmad Azkal Azkiya’ (International Journal of Multidisciplinary Research of Higher Education, 2026)
The purpose of this study is to analyze how the implementation of servant leadership by madrasah principals can effectively encourage teacher collaboration while improving student academic learning outcomes. This study employed a qualitative approach, utilizing a single case study. Data were collected through in-depth interviews (with the principal, deputy principal for curriculum, senior teachers, administrative staff, homeroom teachers, and students) with 15 informants, participant observation, and documentation including the annual work plan, minutes of teacher coordination meetings, and a recapitulation of student report card grades. Data analysis was carried out through reduction, presentation, and drawing conclusions from documents including the annual work plan, minutes of teacher coordination meetings, and a recapitulation of student report card grades. The results show that the principal of one of the Islamic schools applies servant leadership based on spiritual and Islamic principles. Its five pillars (spiritual exemplarity, Islamic empathy, teacher innovation empowerment, Khādimul Ma'had Stewardship, and active hearing) transform the madrasah. This leadership fosters collaboration, integrity, and loyalty, which have been proven to improve student discipline and academic achievement. The contribution of this study is to present a contextual and applicable Servant Leadership model within a spiritual framework (Islamic exemplarity and Khādimul Ma'had Stewardship) in Islamic educational institutions.